2022
DOI: 10.1159/000524270
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Diagnosis of Aggressive Small-Cell Lymphomas

Abstract: <b><i>Background:</i></b> Despite their sometimes deceivingly bland appearance, some small-cell lymphomas are very aggressive and the prognosis of patients depends on a prompt diagnosis that allows the initiation of appropriate therapy. <b><i>Summary:</i></b> The present review discusses the salient cytological features of the most common aggressive small-cell lymphomas and then proceeds to analyze their main diagnostic criteria, including the usage of ancillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 91 publications
(137 reference statements)
0
4
0
Order By: Relevance
“…More recent studies have indicated that FNAC can accurately diagnose lymphoma in 85-90% of patients, particularly when ancillary techniques complement morphological assessment [8,9]. Ancillary techniques, such as immunohistochemistry (IHC), can overcome these difficulties and support the interpretation of cytological diagnoses [10,11]. However, the role of FNAC in the initial diagnosis and subclassification of primary lymphoid malignancy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have indicated that FNAC can accurately diagnose lymphoma in 85-90% of patients, particularly when ancillary techniques complement morphological assessment [8,9]. Ancillary techniques, such as immunohistochemistry (IHC), can overcome these difficulties and support the interpretation of cytological diagnoses [10,11]. However, the role of FNAC in the initial diagnosis and subclassification of primary lymphoid malignancy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Fine needle aspiration cytology (FNAC) is a rapid, safe, minimally invasive and highly accurate diagnostic tool for evaluating benign and malignant conditions 1–8 in various superficial and deep‐seated organs, including lymph nodes 9–12 . The incorporation of rapid on‐site evaluation (ROSE) further enhances its utility by gauging sample adequacy, leading to a notable decrease of approximately 20% in inadequate rates 4,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Fine needle aspiration cytology (FNAC) is a rapid, safe, minimally invasive and highly accurate diagnostic tool for evaluating benign and malignant conditions [1][2][3][4][5][6][7][8] in various superficial and deep-seated organs, including lymph nodes. [9][10][11][12] The incorporation of rapid onsite evaluation (ROSE) further enhances its utility by gauging sample adequacy, leading to a notable decrease of approximately 20% in inadequate rates. 4,13 The precision of FNAC's diagnostic outcomes is augmented through immunocytochemistry (ICC) on diverse substrates such as cell block (CB), liquid-based cytology (LBC) or smears, along with molecular testing, [14][15][16][17] and flow cytometry (FC) for lymphoproliferative processes.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular techniques and immunohistochemical techniques are important to further characterize cytomorphologically difficult cases diagnosed as lymphoproliferative disorders. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Molecular techniques and immunohistochemical techniques are important to further characterize cytomorphologically difficult cases diagnosed as lymphoproliferative disorders. 3,4 FNAC technique was initially introduced in the early 1900's. 5 FNAC involves collecting cells by aspirating the affected organ or tissue using a thin needle to study them under a microscope after appropriate staining.…”
Section: Introductionmentioning
confidence: 99%